Realitäten des Glaubens: zur virtuellen Dimension christlicher Religiosität - Nord, Ilona (Praktische Theologie im Wissenschaftsdiskurs, 2008)
Virtual realities are computer-mediated communication spaces. They are also to be found in religion. In its first part, the volume contains contributions to a practical theological understanding of virtual realities. The second part is concerned with liturgy and preaching from the perspective of media theory. The volume demonstrates how closely media and religion or faith are related to each other where the perception of reality is concerned. Christian religion and Christian faith deal with reality in a constructive manner. Ilona Nord, Westfälische Wilhelms-Universität Münster.